The method of calculating the minimum creep rate of turbine blades of gas turbine engines based on the degradation of the alloy microstructure - Y. V. Petrov; O. A. Ratenko; V. K. Kharina (Научный вестник МГТУ ГА, 2023)
In the current global economic conditions, airlines need to curtail financial expenses. It is known that the share of airline costs for maintenance and repair (MR) in the total cost structure amounts to at least 20%, of which more than 40% is for the repair and maintenance of aircraft engines (AE). According to the actual expertise, this item of expenditure will continue to grow due to the inevitable sophistication of AE structures, which is specified by the need to increase the efficiency and ecological compatibility. One of the possible ways of curbing maintenance and repair expenses is to transit for the operation of on-condition components which are currently in operation until the overhaul life is exhausted. For example, turbine blades of gas turbine engines (GTE) can be pertinent to such elements. It is a common fact that turbine blades operate in challenging environment: they are affected by excessive temperatures, severe centrifugal loads, aggressive gas media, and their destruction generally occurs because of the accumulation of fatigue damage and creep. The alloy microstructure significantly degrades and deforms before macroscopic damage develops. The early detection of microscopic damage in the alloy is the tool which allows for the transition to GTE oncondition turbine blades operation. The article presents the method for calculating the minimum creep rate of the Inconel 738LC alloy based on microstructural changes under operating conditions. The obtained results are proposed to be used for calculating the residual life of turbine blades by the creep parameter.